Predicting anxiety and depression among family carers of people with Chronic Obstructive Pulmonary Disease. (July 2014) - Jácome, Cristina; Figueiredo, Daniela; Gabriel, Raquel; Cruz, Joana; Marques, Alda
ABSTRACT Background: Chronic Obstructive Pulmonary Disease (COPD) can be highly incapacitating, imposing a significant burden on family members, however, limited research has been conducted on psychological health of family carers. Thus, this study examined anxiety and depression symptoms in family carers of people with COPD and their predictors. Methods: A cross-sectional study was conducted with family carers and respective patients with COPD. The caregiving situation and the perceived burden, through the Carers' Assessment of Difficulties Index, were collected from family carers. Patients' COPD severity and activities limitation were assessed. The Hospital Anxiety and Depression Scale (HADS) was used to assess anxiety and depression symptoms in family carers and patients. Scores ≥8 were considered clinically significant. Results: A total of 203 family carers (58.2 ± 14.8 years old; 75.4% female) and respective patients with COPD (69.2 ± 11.5 years old; 36.5% female) were included. Clinically significant anxiety symptoms (HADS-anxiety ≥8) were present in 63.5% (n = 129) of family carers, depression symptoms (HADS-depression ≥8) were in 34% (n = 69) and both were in 27.1% (n = 55). Perceived burden [odds ratio (OR) 1.04, 95% confidence intervals (CI) = 1.01–1.06; 1.05, 95% CI = 1.03–1.07] and patients' activities limitation (OR 1.32, 95% CI = 1.01–1.79; 1.41, 95% CI = 1.01–1.96) were significant predictors of anxiety and depression symptoms. Anxiety symptoms were also predicted by female gender (OR 0.33, 95% CI = 0.16–0.66) and depression symptoms by older age (OR 1.03, 95% CI = 1.01–1.06). Conclusion: Family carers of patients with COPD experience anxiety and depression symptoms. Perceived burden, female gender, older age, and patient's activities limitation were predictors of these distressing symptoms. These findings highlight the need to address family carers' needs, namely by investigating the effectiveness of supportive interventions on family's psychological health.